Prevalence of and Associated Factors with Uncontrolled Hypertension Among Middle-Aged Adults’ Hypertensive Patients in Northeast Thailand - Glingasorn, Arunrat Puncha; Sornlorm, Kittipong (Journal of Health Science and Alternative Medicine, 2024)
Introduction: Numerous connected factors influence uncontrollable hypertension. Identifying elements influencing blood pressure regulation can provide valuable insights for addressing this issue. This study aimed to explore the prevalence of and identify the factors associated with uncontrolled hypertension among middle-aged adults living in northeast Thailand. Methods: A cross-sectional study was conducted for data collection between January and March 2023. The study population was HT patients. Descriptive statistics and multiple logistic regression were used for data analyses with a significance level 0.05. Results: The majority were females (67.84%), and the overall prevalence of uncontrolled hypertension was 37.76% (95% CI = 30.11-46.07). In the multivariable logistic regression, five (5) variables were found to be associated with uncontrolled hypertension: inadequate/problematic applied health information (Adjusted odds ratio (AOR) = 6.09; 95%CI=1.51-8.45), knowledge on herbs for hypertension treatment (AOR=5.33; 95%CI=2.04-13.91), education (AOR=5.06; 95%CI=1.87-13.79), household income (AOR=4.98; 95%CI=2.01-12.33), and drinking use (AOR=2.13; 95%CI=1.01-4.40). Conclusion: It is crucial to promote awareness of self-care practices among individuals with uncontrolled hypertension, especially those who engage in alcohol use, individuals with high income, and those with higher educational attainment. Keywords: Uncontrolled, Hypertension, Prevalence, Associated factors, Middle-aged adults